Defining Law Enforcement's Role in Protecting American Agriculture From Agroterrorism in Kansas, Oklahoma, and Texas, 2003-2004 - Knowles, Terry ([Verlag nicht ermittelbar], 2013)
The study was conducted to determine law enforcement's role in protecting American agriculture from terrorism. In particular, the study looked at what effect a widespread introduction of Foot and Mouth disease to America's livestock supply would have on the nation's economy, and law enforcement's ability to contain such an outbreak. The study had two primary components. One component of the study was designed to take an initial look at the preparedness of law enforcement in Kansas to respond to such acts. This was done through a survey completed by 85 sheriffs in Kansas (Part 1). The other component of the study was an assessment of the attitudes of persons who work in the livestock industry with regard to their attitudes about vulnerabilities, prevention strategies, and working relationships with public officials and other livestock industry affiliates. This was done through a survey completed by 133 livestock industry members in Kansas (Parts 2-3, 6-9, 12-13), Oklahoma (Parts 4, 10, 14), and Texas (Parts 5, 11, 15).